2016
DOI: 10.1186/s13705-016-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of bioenergy in North Carolina and Tennessee

Abstract: Background: The goal of the study is to examine the general public's understanding and perceptions of bioenergy and biofuels in North Carolina (NC) and Tennessee (TN). The study focuses on the public concerns, support and risk evaluations of alternative bioenergy feedstocks and biofuels, and includes an assessment of the economic, environmental, social, and policy impacts of bioenergy production and use. Methods: A sample of consumers in NC and TN were surveyed in the fall of 2013 and spring of 2014 for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Biomass source uncertainty may lead the public to initially oppose a project because of concerns over harvest intensity and other ecological risks . The results of the study also corroborated previous work that indicated bioenergy familiarity , perceived benefits to society (Marciano et al, 2014;Radics et al, 2016), specifically job creation , greenhouse gas sequestration (Marciano et al, 2014), and enhancing young community members' ability to stay in the community are positively related with support bioenergy systems. These findings align with many of the arguments for bioenergy production, such as climate change mitigation and economic development.…”
Section: Support For Forest Biomass Production: Sources Mattersupporting
confidence: 85%
“…Biomass source uncertainty may lead the public to initially oppose a project because of concerns over harvest intensity and other ecological risks . The results of the study also corroborated previous work that indicated bioenergy familiarity , perceived benefits to society (Marciano et al, 2014;Radics et al, 2016), specifically job creation , greenhouse gas sequestration (Marciano et al, 2014), and enhancing young community members' ability to stay in the community are positively related with support bioenergy systems. These findings align with many of the arguments for bioenergy production, such as climate change mitigation and economic development.…”
Section: Support For Forest Biomass Production: Sources Mattersupporting
confidence: 85%
“…This urgency may greatly increase demand for forest harvest residue as feedstock for bioenergy and bioproducts. If so, then biomass harvesting guidelines, as part of broader sustainable forest management practices, should help alleviate public concerns about protecting environmental and social values [193], build trust [194] in forest management and governance processes [195,196] and help forest managers meet marketplace standards for sustainability. While global trade in sustainable commodities is typically governed through certification schemes or importation criteria [197][198][199], guidelines help ensure that these higher-level standards are measurable and acceptable, and that global trade is fair.…”
Section: Discussionmentioning
confidence: 99%
“…In context of consumer acceptance, the recent survey on the acceptance towards B7 biodiesel implementation in Malaysia indicates that most of the respondents in Central region of Peninsular Malaysia are aware or have heard about the biodiesel, and agreed that the biodiesel is a renewable energy; nevertheless, only few of them know about the current B7 national programme and technical know-how of the biodiesel, as well as reluctance to pay more for the biofuel [23]. Accordingly, low support of the biomass energy is plausibly due to limited knowledge on the biofuel's operation as well as the lacking in awareness [21,119]. Therefore, this should be addressed to ensure the successfulness of biomass energy deployment and to secure future demand.…”
Section: Challenges Of Biomass Energy Implementation and Mitigation: Malaysia Perspectivesmentioning
confidence: 99%